Performance Characteristics of Lactating Djallonké Ewes Fed Rice Straw Basal Diets Supplemented With Stylosanthes Hamata (Journal of Science and Technology, 2016)
A 7-week feed intake and growth performance study involving thirty lactating Djallonké ewes and their lambs was conducted. The ewes were randomly assigned to 3 dietary treatment groups resulting in 10 replications. The ewes were individually housed and offered 1000 g rice straw basal diet daily; Stylosanthes hamata given as a supplement at one of the 3 rates, which formed the treatments; i.e. 180 g/d [T180], 240 g/d[T240] or 360 g/d [T360]. Feed intake of the ewes and liveweight changes of the ewes and their lambs were recorded. Intake of rice straw was similar amongst the ewes on the differenttreatments (P>0.05). However, the ewes consumed more supplement as the amount offered increased resulting in a significant improvement in total feed intake as the supplement offered increased (P< 0.01). There was no significant difference (P>0.05) in the body weights of the ewes that could be attributable to treatment effects. The average daily gains (ADG) at day 49 for the lambs were, 47.5 [T180], 63.4 [T240] and 76 g [T360]. This result suggest that supplementation of ewes had a significant effect (P